Chronicle of international labor jurisprudence 2022 - Arias Domínguez, Ángel (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
In calendar year 2002, no resolutions of the Committee on Freedom of Association have been issued that affect Spain.None of the four ECHR rulings to which Spain was a party had labor, social security or social protection content.There are, as usual, CJEU resolutions with a social content in which the Spanish state has been a party, but, unlike previous years, there have not been so many pronouncements, nor have they been of such importance.Of the various matters that resolve preliminary rulings that the CURIA database returns, two have been analyzed in which the Spanish state has been involved, and one more related to the projection of religious symbols in the work that due to its technical configuration can have an easy projection for our legal system.As usual, the conceptual thesauruses used for the search in the institutional database have been the following: “Social security”, “Public health”, “Social policy”, “non-discrimination”, “Free movement of workers”, “Freedom of establishment”, “European Social Fund (ESF)”, “Employment”, “Education, professional training and youth”, “Statute of civil servants and regime applicable to other agents”, “Fundamental rights”, “Economic cohesion , social and territorial”, and “Citizenship of the Union”.The very interesting STJUE of February 24, 2022 [C-389/20] CJ and TGSS, decides that our internal legal rule that prevented contributions for the contingency of unemployment in the security system is not in accordance with the community regulations on equality household employees social. The legal consequence was evident, the ipso facto modification of said rule. The STJUE of April 28, 2022 [C-86/21] Regional Health Management of Castilla y León and Delia, analyzes to what extent an autonomous regulation of professional performance evaluation can stop considering the professional activity carried out in another Union country. The negative answer is very intuitive, but the analysis of the resolution serves to outline or clarify the community demands that are imposed on the restriction sought by the national law.The most interesting STJUE of October 13, 2022 [C-344/20] L.F. and S.C.R.L. addresses a major issue for modern secular states: the legitimacy of the business restriction on the use by workers of garments that unequivocally manifest a certain religious conviction.